Primary Pleomorphic Undifferentiated Sarcoma—a Rare Renal Localization: A Case Report - Soufiane Mellas; Ahmed Amine Bouchikhi; Mohamed-Fadl Tazi; Abdelhak Khallouk; Jallal-Eddin Elammari; Mohamed-Jamal El Fassi; Naoufal Mellas; Moulay Hassan Farih (Case Reports in Urology)
Undifferentiated pleomorphic sarcoma is known as a soft tissue sarcoma. Very few cases of this tumor originating from the renal parenchyma or renal capsule have been reported. We report a case of a 70-year-old patient admitted for enormous ureterohydronephrosis and pyelonephritis due to a pelvic ureter lithiasis. After draining by ureteral double J catheter, a nephroureterectomy was performed for nonfunctional kidney confirmed by scintigraphy. The histopathological study shows a pleomorphic undifferentiated sarcoma. The patient was sent to oncologists. Chemotherapy was proposed but the family decided to stop the treatment. The patient passed away 10 months later. Clinicians and pathologists should be aware of the very low occurrence of this renal tumor, which is extremely rare. Currently there is no consensus about its management. Our case extends the literature concerning this tumor.